On (k,m)-n-Paranormal Operators - Mohsen, Salim Dawood (Iraqi Journal of Science, 2023)
The new type of paranormal operators that have been defined in this study on the Hilbert space, is paranormal operators. In this paper we introduce and discuss some properties of this concept such as: the sum and product of two paranormal, the power of paranormal. Further, the relationships between the paranormal operators and other kinds of paranormal operators have been studied.